Analisis Sudut Pulley dan Berat Rol Transmisi Terhadap Torsi Sepeda Motor Matic 150 Cm3 - Aldi Dwi Nurwanto; Syamsul Hadi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The purpose of this study was to determine the effect of pulley angle variations of 13.5ᵒ and 14ᵒ and roller weight variations of 12 g, 14 g, and 16 g on the torque of a 150 cm3 automatic motorcycle. The method with a quantitative approach the method used is the experimental method. For the sample of this research is a type of pulley and 3 types of rollers with different slopes and weights where the angle varies to test the 150 cm3 matic motorcycle torque used. From the results of this study results in a value where the Fcount value is greater than the Ftable means that the null hypothesis (H02) is rejected and the alternative hypothesis (H22) is accepted or the mass of the roller has an influence on torque, the Fcount value is greater than the Ftable means that the hypothesis (H01) is rejected and the alternative hypothesis (H11) is accepted or the mass of the roller has an influence on torque, and that the interaction between pulley angle and roller mass does not affect, and the Ftable value is lower than the Fcount value that the hypothesis (H03) is accepted and the alternative hypothesis (H33) is rejected, roller mass affects torque.